1984
DOI: 10.1016/s0022-5371(84)90093-8
|View full text |Cite
|
Sign up to set email alerts
|

Cue validity and sentence interpretation in English, German, and Italian

Abstract: Cue validity and sentence interpretation in English, German, and Italian U n i v e r s i t ä t P o t s d a mHumanwissenschaftliche Fakultät fi rst published in:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

23
379
4
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 393 publications
(409 citation statements)
references
References 20 publications
23
379
4
3
Order By: Relevance
“…A limitation of this proposal, however, is that it does not capture the effects of the edit distance to a sentence string with a plausible meaning on people's reliance on syntax. As we have seen here, when the edit distance is relatively large (for example, between an active structure and a passive structure), people tend to interpret the string literally, even if the content is implausible (29). However, when the edit distance between two alternatives is smaller-as in the double-object/prepositional phrase object alternations or the transitive/intransitive alternations-people have a greater tendency to interpret the string according to the more plausible alternative.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…A limitation of this proposal, however, is that it does not capture the effects of the edit distance to a sentence string with a plausible meaning on people's reliance on syntax. As we have seen here, when the edit distance is relatively large (for example, between an active structure and a passive structure), people tend to interpret the string literally, even if the content is implausible (29). However, when the edit distance between two alternatives is smaller-as in the double-object/prepositional phrase object alternations or the transitive/intransitive alternations-people have a greater tendency to interpret the string according to the more plausible alternative.…”
Section: Discussionmentioning
confidence: 59%
“…The cue integration approach proposed in the competition model (29) is similar in spirit to a noisy-channel model in its assumption of noise in the input and its reliance on the integration of information from a variety of sources. However, the specific cue integration approach proposed in the competition model does not appear to be quite consistent with the observed results.…”
Section: Discussionmentioning
confidence: 99%
“…In the same task, the children's performance was better than chance if the whole of the sentence was presented. The cross-linguistic data reported by a number of researchers on sentence interpretation (Bates et al, 1982;Kail, 1989;Kilborn & Cooreman, 1987;MacWhinney, Bates, & Kliegl, 1984;McDonald & Heilenman, 1991) are also compatible with this view. Theses authors used a sentence interpretation paradigm in which subjects were required to choose the subject/agen t of a sentence with a structure like (14) (from MacWhinney et al, 1984, p. 139): 14a.…”
Section: Discussionmentioning
confidence: 62%
“…MacWhinney et al (1984) found that Italian speakers relied on agreem ent to make decisions about the subject/agent of the sentence, while English speakers relied overwhelm ingly on word order. Dutch, French and Spanish behave like Italian in this respect: Kilborn and Cooreman (1987) showed that speakers of Dutch rely more on agreement than on word order, and Kail (1989) and McDonald and Heilenman (1991) showed the same for French and Spanish.…”
Section: Discussionmentioning
confidence: 99%
“…We have studied the use of these cues in Arabic (Taman, 1993), Bulgarian (Andonova, 1998), Chinese (Bates, Chen, Tzeng, Li, & Opie, 1991;Li, Bates, Liu, & MacWhinney, 1992;Tzeng, Chen, & Hung, 1991), Dutch (Kilborn & Ito, 1989;McDonald, 1986;McDonald, 1987a;McDonald, 1987b), English (Bates, McNew, MacWhinney, Devescovi, & Smith, 1982;MacWhinney & Bates, 1978;MacWhinney, Bates, & Kliegl, 1984), French (Kail, 1989), Hebrew (Sokolov, 1989), Hindi (Vaid & Pandit, 1991), Hungarian MacWhinney, OsmanSági, & Slobin, 1991;MacWhinney & Pléh, 1988;MacWhinney & Pléh, 1997;MacWhinney, Pléh, & Bates, 1985), Italian Bates et al, 1982), Japanese (Kilborn & Ito, 1989;Sasaki, 1994;Sasaki, 1997a;Sasaki, 1997b), Russian (Kempe & MacWhinney, 1998), Spanish (Kail, 1989), Turkish (MacWhinney et al, 1991), and Warlpiri (Bavin & Shopen, 1989).…”
mentioning
confidence: 99%